Calculation of the System Focusing Electron Beam in the Ion Source of Mass Spectrometer with Electron Impact Ionization - О.S. Kuzema; P.O. Kuzema (Журнал нано- та електронної фізики)
It has been found the correlations for the parameters of electron movement and it has been determined the value for magnetic induction in the region of ionization chamber providing the electron beam passage through the space of ionization chamber without its broadening.